2015
DOI: 10.1007/s00592-015-0713-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for severe and symptomatic hypoglycemia in type 1 diabetes. Results of the HYPOS-1 study

Abstract: Fewer than 20 % of T1DM patients are free from hypoglycemia, with one in six having experienced at least one severe episode in the last year. The distribution is uneven, with a tendency of episodes to cluster in some patients. Severe and symptomatic episodes have different correlates and reflect different conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 25 publications
4
68
1
4
Order By: Relevance
“…CAD, infection, and poor renal function have been reported to be associated with risks of recurrent hypoglycemia [31]. The HYPOS-1 study reported the rate of hypoglycemia was higher in patients with previous severe hypoglycemia, neuropathy, long duration, and on polypharmacy [18]. Therefore, patients with more comorbidies are at risk for recurrent hypoglycemia and should be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CAD, infection, and poor renal function have been reported to be associated with risks of recurrent hypoglycemia [31]. The HYPOS-1 study reported the rate of hypoglycemia was higher in patients with previous severe hypoglycemia, neuropathy, long duration, and on polypharmacy [18]. Therefore, patients with more comorbidies are at risk for recurrent hypoglycemia and should be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, polypharmacy and anti-diabetic agents are identified as risk factors for hypoglycemia. In HYPOS-1 study, polypharmacy was associated with a 24% excess of risk for hypoglycemia [18]. Hypoglycemia episodes were higher among those with insulin and insulin secretagogues [15, 27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Association of HbA 1c levels with hypoglycemia has varied in different studies (30)(31)(32). Viewing the analysis by updated data in our study, an inverted U-shaped curve was observed for any hypoglycemia by HbA 1c categories in patients with use of insulin or of SUR without insulin.…”
Section: Discussionmentioning
confidence: 99%
“…3 Structured diabetes education delivered in routine practice for persons with type 1 diabetes have been found to at least halving rates of severe hypoglycaemia (SH) 4 and lead to reduced emergency treatment costs. 5 Past experience of SH is associated with greater fear of hypoglycaemia (FoH) in individuals with type 1 diabetes, suggesting that the experience of hypoglycaemia plays an important role in triggering FoH.…”
mentioning
confidence: 99%